2021
DOI: 10.1002/biof.1712
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of NRF2 attenuates myocardial ischemia reperfusion injury through mediating microRNA‐29a‐3p/CCNT2 axis

Abstract: Accumulated studies have been implemented for comprehending the mechanism of myocardial ischemia reperfusion injury (MI/RI). Nuclear factor erythroid-2 related factor 2 (NRF2)-mediated transcription activity in MI/RI has not been completely interpreted from the perspective of microRNA-29a-3p (miR-29a-3p) and cyclin T2 (CCNT2). Therein, this study intends to decode the mechanism of NRF2/miR-29a-3p/CCNT2 axis in MI/RI. Rat MI/RI models were established by left anterior descending artery ligation. Rats were injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…[28][29][30] Mounting evidence shows that activation of Nrf2 protects against H/R-induced cardiac injury in vitro and myocardial ischemiareperfusion injury in vivo. [31][32][33][34] Various factors regulate Nrf2 activation during H/R-induced cardiac injury; however, the precise molecular mechanisms remain largely unknown. CTRP12 has been reported to exert a key role in the regulation of Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Mounting evidence shows that activation of Nrf2 protects against H/R-induced cardiac injury in vitro and myocardial ischemiareperfusion injury in vivo. [31][32][33][34] Various factors regulate Nrf2 activation during H/R-induced cardiac injury; however, the precise molecular mechanisms remain largely unknown. CTRP12 has been reported to exert a key role in the regulation of Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo myocardial I/R model (60min LAD coronary artery ligation followed by reperfusion as previously shown [ 27 ]), according to the reported study, successful reperfusion was confirmed by the changes in the myocardium color and ECG [ 28 ]. Echocardiography suggested that compared with the sham surgery group, cardiac function deteriorated according to the parameters including decreased EF% and FS% as well as increased LVEDD, LVESD, LVEDV, and LVESV.…”
Section: Resultsmentioning
confidence: 79%
“…Several studies have previously reported the involvement of miR-29a-3p in ischemia/reperfusion-induced cell injury and its function in diverse disease context [ 33 ]. For example, nuclear factor erythroid-2 related factor 2 (NRF2) transcriptionally elevated the expression of miR-29a-3p and suppressed cardiomyocyte apoptosis, oxidative stress, and serum inflammation via suppressing CCNT2 in rats with myocardial ischemia reperfusion injury [ 34 ]. Shen and his colleagues suggested that overexpression of miR-29a-3p that delivered by bone marrow mesenchymal stem cells to target the expression of Ireb2 and consequently reduced the Fe 2+ level and inhibited ferroptosis in hepatic ischemia-reperfusion injury [ 35 ].…”
Section: Discussionmentioning
confidence: 99%